Effect of low pH on growth and shell mechanical properties of the Peruvian scallop Argopecten purpuratus (Lamarck, 1819). (May 2022) - Córdova-Rodríguez, Kathy; Flye-Sainte-Marie, Jonathan; Fernández, Ernesto; Graco, Michelle; Rozas, Anibal; Aguirre-Velarde, Arturo
Abstract: Dissolution of anthropogenic CO2 modifies seawater pH, leading to ocean acidification, which might affect calcifying organisms such as bivalve mollusks. Along the Peruvian coast, however, natural conditions of low pH (7.6–8.0) are encountered in the habitat of the Peruvian scallop ( Argopecten purpuratus ), as a consequence of the nearby coastal upwelling influence. To understand the effects of low pH in a species adapted to these environmental conditions, an experiment was performed to test its consequences on growth, calcification, dissolution, and shell mechanical properties in juvenile Peruvian scallops. During 28 days, scallops (initial mean height = 14 mm) were exposed to two contrasted pH conditions: a control with unmanipulated seawater presenting pH conditions similar to those found in situ (pHT = 7.8) and a treatment, in which CO2 was injected to reduce pH to 7.4. At the end of the experiment, shell height and weight, and growth and calcification rates were reduced about 6%, 20%, 9%, and 10% respectively in the low pH treatment. Mechanical properties, such as microhardness were positively affected in the low pH condition and crushing force did not show differences between pH treatments. Final soft tissue weights were not significantly affected by low pH. This study provides evidence of low pH change shell properties increasing the shell microhardness in Peruvian scallops, which implies protective functions. However, the mechanisms behind this response need to be studied in a global change context. Highlights: Argopecten purpuratus shell growth was reduced by 9% in low pH exposure. A. purpuratus net calcification was reduced about 10% in low pH exposure. S hell microhardness of A. purpuratus was positively affected by low pH.